High intake rates of microplastics in a Western Atlantic predatory fish, and insights of a direct fishery effect. (May 2018) - Ferreira, Guilherme V.B.; Barletta, Mário; Lima, André R.A.; Morley, Simon A.; Justino, Anne K.S.; Costa, Monica F.
Abstract: Microplastic contamination was investigated in the gut contents of an economically important estuarine top predator, Cynoscion acoupa, according to spatiotemporal and ontogenetic use of a tropical estuary. Microplastic contamination was found in more than half of the analysed fish. Ingested microplastics were classified by type, colour and length with most of the particles consisting of filaments (<5 mm). Longer filaments were more frequently ingested in the upper estuary and smaller filaments in the lower estuary, as a result of differences in hydrodynamic forces and proximity to the probable input sources. The river is likely an important source of filaments to the estuary and filaments ingested in the upper estuary showed little sign of weathering, when compared with those from the lower estuary, which are subject to intense weathering and consequent break-up of particles to smaller sizes. Most filaments, of all colours, accumulated in adults of C. acoupa, which are more susceptible to contamination through both direct ingestion and trophic transference as they shift their feeding mode to piscivory. Moreover, the highest ingestion of filaments in adults occurred in the lower estuary, during the late rainy season, likely associated with the intense fishing activities in this habitat, which results in a greater input of filaments from fishing gear, which are mainly blue in colour. Overall, 44% of the ingested filaments were blue, 20% purple, 13% black, 10% red and 12% white. The next most common colour, the purple filaments, are most likely blue filaments whose colour has weathered to purple. Red filaments were proportionally more ingested in the lower estuary, indicating a coastal/oceanic source. White and black filaments were more commonly ingested in the inner estuary, suggesting that they have a riverine origin and/or were actively ingested by juveniles and sub-adults, which inhabit the inner estuary and have zooplankton as an important food resource. Graphical abstract: Image 1 Highlights: Environmental dynamics and fish ontogeny influenced the types of microplastics ingested. Length of filaments is correlated with the salinity gradient. Colour of filaments ingested are linked to the ecological groups of prey. Trophic level has an important role in contamination rates. Top predators are more vulnerable to microplastic contamination. Abstract : Environmental gradients and ecological interactions are responsible for the patterns of ingestion of the different colours and lengths of filaments by Cynoscion acoupa .